Analysis of learning cycles in participatory environment and development projects: lessons from Nepal - Hiyama, C.; Keen, M. (Australian National University, 2004)
In this paper, the authors assess the extent to which the inclusion of learning cycles in community development projects can contribute to local people’s increased capacity to initiate action. A case study approach was used to test the hypothesis that: Participatory environment and development projects that incorporate learning cycles will result in empowerment among local people. In this research, learning cycles were defined as a ‘continuous process of situation analysis, collaborative planning, action and critical reflection’ (see Section 3.4), while empowerment was defined as ‘a process through which individuals, as well as local groups and communities, enhance their capacity to initiate action to improve their well-being by gaining decision-making power’ (see Section 2.2). Six key research questions were formulated to ensure that all these components were considered when testing the hypothesis (Section 4). The case study involved two sub-projects of a community development and forest/watershed conservation project conducted in the mid-hills of Nepal by the Nepalese Government and the Japan International Cooperation Agency (JICA). In the sections to follow the relationship between participatory development projects and learning cycles are explored. Section 2 defines participatory development and empowerment in more depth, while Section 3 reviews three learning theories—experiential learning, social learning and organisational learning (in particular, multi-looped learning) —to build the analytical framework for the case study. Section 4 describes the research methods, including criteria for selection of case studies, and the field survey methods. Section 5 reports the qualitative field data, and discusses the extent to which the case study projects demonstrated learning cycles. Section 6 discusses these results further and presents conclusions.